2010
DOI: 10.1111/j.1365-2036.2010.04493.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: MiraLAX vs. Golytely – a controlled study of efficacy and patient tolerability in bowel preparation for colonoscopy

Abstract: SUMMARY BackgroundMiraLAX is gaining acceptance as a bowel cleanser for colonoscopy. We hypothesize that MiraLAX ⁄ Gatorade is as efficacious for bowel cleansing as Golytely and is more tolerable for patients undergoing screening colonoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 20 publications
(23 reference statements)
0
55
0
2
Order By: Relevance
“…Today we have a combination of sodium picosulfate magnesium oxide and citric acid (CitraFleet ® ) (26,27) and bisacodyl (Dulcolaxo ® ) (28,29). Its effectiveness lies in 70-80% of patients, but may be associated with electrolyte problems and dehydration.…”
Section: Stimulating Agentsmentioning
confidence: 99%
“…Today we have a combination of sodium picosulfate magnesium oxide and citric acid (CitraFleet ® ) (26,27) and bisacodyl (Dulcolaxo ® ) (28,29). Its effectiveness lies in 70-80% of patients, but may be associated with electrolyte problems and dehydration.…”
Section: Stimulating Agentsmentioning
confidence: 99%
“…Studies have shown the quality of split dose Miralax bowel preparation is inferior compared to the 4L split dose Golytely for screening colonoscopies. 19,20 Options Comments Adding metoclopramide (5 to 10 mg) orally to prevent or treat nausea…”
Section: Flavored Peg Solutionsmentioning
confidence: 99%
“…Bowel preparation remains a major deterrent to patient compliance with CRC screening guidelines (9). At least 5%-15% of patients do not complete their bowel preparation because of the (10). In an effort to improve patient tolerability and adherence, reduced-volume 2-L polyethylene glycol-ascorbic acid (PEG-AA) and electrolyte lavage solutions (ELSs) are now available, with ascorbic acid acting as an additional cathartic and flavoring agent.…”
Section: Introductionmentioning
confidence: 99%
“…One study using PEG-3350 in a community setting resulted in good-quality bowel preparations and patient tolerability (14). Subsequent studies compared PEG-3350+SD with 4-L PEG-ELS, some concluding PEG-3350 as a non-inferior bowel preparation (15)(16)(17), while others showed higher quality preparations with 4-L PEG-ELS (10,18). There have been no head-tohead comparative trials of PEG-3350+SD+B vs. PEG-AA.…”
Section: Introductionmentioning
confidence: 99%